Utilization of Adolescent Information and Counseling Centers (PIK-R) on Knowledge, Attitudes and Behaviors About Premarital Sex in Nursing Study Program Students Mulawarman University Faculty of Medicine Samarinda City - Sari, Rita Puspa; Ruminem, Ruminem; Nopriyanto, Dwi; Sholichin, Sholichin; Khumaidi, Khumaidi; Muda, Iskandar (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Background: Youth PIK is a place for reproductive health services for adolescents developed by the government in the GenRe program, which is managed by and for adolescents. This PIK youth service provides benefits by providing information and counseling services on maturing marriage age, eight family functions, TRIAD KRR (sexuality, HIV and AIDS, and NAFZA), life skills (life skills), gender and advocacy skills, and IEC. Utilization of the Adolescent Counseling Information Center is greatly influenced by the level of knowledge, reflection of adolescent attitudes, motivation from the surrounding environment, peer support, and teacher support so that the incidence of premarital sex behavior, which is bad for adolescents, can be reduced.Objective: to identify the relationship between the utilization of information and youth health centers (PIK-R) towards adolescents in terms of knowledge level, attitudes, and premarital sexual behavior. This research is also expected to bring benefits to PIK-KRR organizational managers in the campus environment by directing activities that can become part of PIK-KRR activities to improve their functions.Methods: This research is a descriptive correlation study using a cross-sectional research design and a quantitative approach with a sample of 175 respondents. The data analysis used was the Chi-Square statistical test and the Spearman test to see the strength of the relationship.Results: In the Chi-Square analysis, the results show that there is a relationship between the PIK-R utilization variables and the level of knowledge (ρ- value 0.031 < 0.05) with the category of weak relationship strength (correlation coefficient = 0.163 in the range between 0.10-0, 29) and the relationship is unidirectional. The results of the analysis of the relationship between the utilization of PIK-R variables and attitude show that there is a relationship (ρ -value 0.034 < 0.05) with the category of strength of the weak relationship (correlation coefficient = 0.160 is in the range 0.10-0.29) and the relationship is unidirectional. The results of the analysis of PIK-R utilization and premarital sex behavior showed that there was a relationship (ρ -value 0.025 < 0.05), but the relationship was not in the same direction because the correlation was negative (-0.169).Conclusion: There is a relationship between the variable utilization of information centers and youth counseling (PIK-R) and the variables of knowledge, attitude, and behavior of premarital sex in adolescents.